Personal and perceived peer use and attitudes towards use of non-prescribed prescription sedatives and sleeping pills among university students in seven European countries - AKVARDAR, YILDIZ (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Introduction The use of non-prescribed prescription sedatives and sleeping pills (NPPSSP) among university students has been described as an important public health issue. However, the impact of perceived social norms on students' use and attitudes towards use of NPPSSP is still unclear. Our aim was to investigate whether perceptions of peer use and approval of use are associated with students' personal use and approval of NPPSSP use. Methods: Cross-sectional data from the Social Norms Intervention for the prevention of Polydrug Use (SNIPE) project containing 4482 university students from seven European countries were analyzed to investigate self other discrepancies regarding personal use and attitudes towards NPPSSP use. Associations between personal and perceived peer use and between personal and perceived approval of use were examined using multivariable logistic regression. Results: The majority (51.0%) of students perceived their peers' NPPSSP use to be higher than their personal use. 92.6% of students perceived their peers' approval of NPPSSP use to be identical or higher than their personal approval. Students perceiving that the majority of peers had used NPPSSP at least once displayed higher odds for personal lifetime use (OR: 1.95, 95% CI: 1.49-2.55). Perceived peer approval of NPPSSP use was associated with higher odds for personal approval (OR: 5.49, 95% CI: 4.63-6.51). Conclusions: Among European university students, perceiving NPPSSP use and approval of use to be the norm was positively associated with students' personal NPPSSP use and approval of use, respectively. Interventions addressing perceived social norms may prevent or reduce NPPSSP use among university students.
Keywords: University students; Non-medical use; Sedatives; Sleeping pills; Perceptions; Social norms; COLLEGE-STUDENTS; DRUG-USE; NORMATIVE PERCEPTIONS; ACADEMIC-PERFORMANCE; NONMEDICAL USE; YOUNG-ADULTS; ALCOHOL-USE; MISPERCEPTIONS; NORMS; PREVENTION